Epidemiological analysis of dengue cases in Alagoas, from 2020 to 2024 (Research, Society and Development, 2025)
Introduction: Dengue, transmitted by the Aedes aegypti mosquito, is an arbovirus with a significant impact in tropical regions such as Alagoas, where socio-environmental conditions favor its spread. Therefore, epidemiological studies are essential to guide public control and prevention policies. Objective: This study aims to conduct an epidemiological analysis of dengue in Alagoas from 2020 to 2024. Methodology: An observational, cross-sectional, ecological design was adopted, using secondary data from SINAN (2020-2024), analyzing variables such as year, geography, sex, confirmation criteria, IgM serology, and clinical classification. Descriptive statistics were applied to calculate relative frequencies, and the results were standardized into tables. Results: Alagoas recorded 0.61% of the national cases. Women predominated (54.62%) over men (45.31%), with the highest incidence in 2022 (28.35% and 22.31%, respectively). Clinical criteria prevailed (82.25%), followed by laboratory criteria (14.70%), while IgM serology was not performed in 93.49% of cases, with only 4.71% positive. Clinical classification revealed 94.96% of cases without warning signs, 2.17% with warning signs, and 0.12% with shock, demonstrating a predominance of mild forms. Conclusion: The increasing trend in cases reflects structural challenges, such as poor sanitation and low serological testing, highlighting the need for investments in surveillance and prevention to reduce the impact of dengue in Alagoas and improve quality of life. Finally, it is necessary to complement this topic with future epidemiological studies.